PERJANJIAN PENGADAAN BARANG DALAM PEMBELIAN ALAT ANGKUT DARAT BERMOTOR ANTARA CV. KANA SURYA SEJAHTERA DENGAN RUMAH SAKIT UMUM DAERAH (RSUD) dr RASIDIN PADANG - Satria Salean, Abd Rahmad , (Normative Jurnal Ilmiah Hukum, 2022)
The purchase of motorized land transportation is useful for carrying patients who need referrals to other hospitals and is equipped with several medical equipment, so it is very much needed by the Rasidin Padang Regional General Hospital (RSUD). The agreement for the procurement of goods in the purchase of motorized land transportation between CV. Kana Surya Sejahtera and RSUD dr Rasidin Padang are guided by Presidential Regulation Number 12 of 2021 Amendments to Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services. The formulation of the problem in this study is how the implementation of the procurement agreement in the purchase of motorized land transportation between CV. Kana Surya Sejahtera with the Regional General Hospital Dr Rasidin Padang?. What are the obstacles in implementing the goods procurement agreement in the purchase of motorized land transportation between CV. Kana Surya Sejahtera with the Regional General Hospital Dr Rasidin Padang? How are the efforts to overcome obstacles in the procurement agreement for the purchase of motorized land transportation between CV. Kana Surya Sejahtera with the Regional General Hospital Dr Rasidin Padang?. The problem approach used in this research is sociological juridical, namely research to see facts in the field associated with applicable regulations. The nature of this research is descriptive, which is to explain facts in the field systematically and logically. The results of the research are the implementation of the agreement through the stages of Procurement Preparation, the Procurement Committee includes in the SPSE, Auction Announcement, Bidder Registration, Auction Explanation, Bid Submission, Evaluation Process, Announcement of Prospective Auction Winners, Rebuttals and Acceptance. The obstacle is that at the preparation stage for the procurement of PA/KPA, it is often too late to set the General Procurement Plan (RUP) so that the Pokja/procurement official does not have a basis for carrying out the procurement. To have a basis for carrying out procurement, there must also be a timetable so that the public auction method can quickly determine the winner